PERAN INOVASI DAN KREATIVITAS DALAM MENINGKATKAN KEUNGGULAN KOMPETITIF UMKM DI KELURAHAN BANTAN - Damanik, M. A. Jaya; Saragih, Vina Gabriela; Annisa, Chitra; Girsang, Deddy Ray (Jurnal Manajemen dan Bisnis, 2025)
This study aims to explore the role of innovation and creativity in enhancing the competitive advantage of Micro, Small, and Medium Enterprises (MSMEs) in Bantan Village, Medan Tembung District. The research focuses on Toko Besi Sadar Jaya, which faces competition from large stores and online marketplaces. Using a qualitative approach and case study method, this study identifies the innovation and creativity strategies implemented, such as product diversification, improving customer service, and utilizing social media for promotion. The findings indicate that product and service innovation, combined with creative marketing, have a significant impact on increasing sales and competitiveness. However, challenges such as limited resources and price competition remain obstacles. This research provides practical contributions for MSME practitioners in adopting innovation and creativity strategies and offers recommendations for future researchers to expand the study to other sectors. Therefore, this study contributes to the development of literature related to innovation and competitiveness in MSMEs in Indonesia.